Sociology’s Next Decades: Centrifugality, Conflict, Accommodation - Smelser, Neil (Cahiers de recherche sociologique)

(untitled) (Département de sociologie - Université du Québec à Montréal, 1990)
SummaryIn this essay, the author proceeds in three steps: first, by identifying some broad societal trends affecting sociology; second, by formulating important directions of change of the discipline suggested by these trends and described by the notion of centrifugality; third, by locating certain lines of conflict within the discipline and bases for accommodation and integration. His essay applies mainly to the American scene with observations applicable to sociology in other parts of the world.